Transcriptional Regulation of Neuronal Genes and Its Effect on Neural Functions: Gene Expression in Response to Static Magnetism in Cultured Rat Hippocampal Neurons - Takao Hirai; Yukio Yoneda (Elsevier, 2005)
We have previously shown a marked but transient increase in DNA binding of the nuclear transcription factor activator protein-1 after brief exposure to static magnetic fields in cultured rat hippocampal neurons, suggesting that exposure to static magnetism would lead to long-term consolidation as well as amplification of different functional alterations through modulation of de novo protein synthesis at the level of gene transcription in the hippocampus. Hippocampal neurons were cultured under sustained exposure to static magnetic fields at 100 mT, followed by extraction of total RNA for differential display (DD) analysis using random primers. The first and the second DD polymerase chain reaction similarly showed the down-regulation of particular genes in response to sustained magnetism. Nucleotide sequence analysis followed by BLASTN homology searching revealed high homology of these 2 DD-PCR products to the 3' non-coding regions of the mouse basic helix-loop-helix transcription factor ALF1 and that of histone H3.3A, respectively. On Northern blot analysis using the 2 cloned differentially expressed fragments labeled with [α-32P]dCTP by the random primer method, a marked decrease was seen in expression of mRNA for ALF1 and histone H3.3A in hippocampal neurons cultured under sustained exposure to static magnetic fields at 100 mT. It thus appears that static magnetism may modulate cellular integrity and functionality through expression of a variety of responsive genes required for gene transcription and translation, proliferation, differentiation, maturation, survival, and so on in cultured rat hippocampal neurons. Keywords:: static magnetic field, activator protein-1, hippocampal neuron, differential display